A chemical-genetics approach to study the role of atypical protein kinase C in Drosophila - Matthew R. Hannaford; Nicolas Loyer; Francesca Tonelli; Martin Zoltner; Jens Januschke (2019)
Studying the function of proteins using genetics in cycling cells is complicated by the fact that there is often a delay between gene inactivation and the timepoint of phenotypic analysis. This is particularly true when studying kinases, that have pleiotropic functions and multiple substrates. Drosophila neuroblasts are rapidly dividing stem cells and an important model system to study cell polarity. Mutations in multiple kinases cause neuroblast polarity defects, but their precise functions at particular time points in the cell cycle are unknown. Here we use chemical genetics and report the generation of an analogue-sensitive (as) allele of Drosophila atypical protein kinase C (aPKC). We demonstrate that the resulting mutant aPKC kinase can be specifically inhibited in vitro and in vivo. Acute inhibition of aPKC during neuroblast polarity establishment abolishes asymmetric localization of Miranda while its inhibition during NB polarity maintenance does not in the time frame of normal mitosis. However, aPKC contributes to sharpen the pattern of Miranda, by keeping it off the apical and lateral cortex after nuclear envelope breakdown.